2020
DOI: 10.1111/age.13015
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing and signatures of selection scan in two Siberian native sheep breeds point to candidate genetic variants for adaptation and economically important traits

Abstract: SummaryRussian sheep breeds represent an important economic asset by providing meat and wool, whilst being adapted to extreme climates. By resequencing two Russian breeds from Siberia: Tuva (n = 20) and Baikal (n = 20); and comparing them with a European (UK) sheep outgroup (n = 14), 41 million variants were called, and signatures of selection were identified. High‐frequency missense mutations on top of selection peaks were found in genes related to immunity (LOC101109746) in the Baikal breed and wool traits (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…For the interbreed CNVRs present either in Baikal or Tuva breeds, almost all (except for two gain events in the Tuva breed) regions were detected in the resequencing set from Sweet‐Jones et al . (2020) (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the interbreed CNVRs present either in Baikal or Tuva breeds, almost all (except for two gain events in the Tuva breed) regions were detected in the resequencing set from Sweet‐Jones et al . (2020) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We also used CNVs of Tuva and Baikal breeds detected from whole‐genome sequencing data (Sweet‐Jones et al . 2020) to check our CNVRs. We performed a simple overlap (1 bp minimum) of coordinates of our interbreed CNVRs (Table ) with Tuva and Baikal breed CNVs detected in the resequencing set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabp9 is typically expressed in the testis (Selvaraj et al 2010), but previous findings have also suggested a role in skin homeostasis in Artiodactyls (Jiang et al 2014). Aadacl3 , although poorly studied, appears to be related with epidermal fat deposition (Lu et al 2020; Sweet-Jones et al 2021). Additionally, analysis of the Human Protein Atlas (www.proteinatlas.org) shows a very specific pattern with expression noted only in skin, breast, and placenta (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Three remaining Welsh sheep resequenced genomes for Welsh Hardy-Speckled Faced, Dolgellau Welsh Mountain, and Talybont Welsh Mountain were downloaded from the National Centre for Biotechnology Information Sequence Read Archive, PRJNA160933 (Heaton et al, 2014). A dataset of resequenced Russian sheep samples (n = 40) adapted to a contrasting environment was used as an outgroup in this study (Sweet-Jones et al, 2021).…”
Section: Data Source and Variant Callingmentioning
confidence: 99%